A cardiac rehabilitation program to improve psychosocial outcomes of women with heart disease - Davidson, Patricia; DiGiacomo, Michelle; Zecchin, R.; Clarke, M.; Paul, G.; Lamb, K.; Hancock, K.; Chang, E.; Daly, J. (Mary Ann Liebert Inc., 2008)
Background: Heart disease in women is characterised by greater disability and a higher rate of morbidity and early death after an acute coronary event as compared to men. Women also have lower participation rates in cardiac rehabilitation than men.Aim: This study sought to describe development of a nurse-directed cardiac rehabilitation program tailored to the needs of women following an acute cardiac event, to address their psychological and social needs.Method: The Heart Awareness for Women program (HAFW) commenced in 2003 with Phase I involving development of program elements and seeking validation through consumers and clinical experts. The program was then trialed in an 8-week program in a convenience sample of six women. Phase II applied the revised program using action research principles focusing on enabling clinical staff to implement the ongoing program. A total of 54 women participated in this phase, 48 of whom completed baseline questionnaires. A mixed-method evaluation, utilizing questionnaires, interviews, and observation, was used to assess the impact of the intervention on psychological and social aspects of women?s recovery following an acute coronary event.Results: Women welcomed the opportunity to discuss their individual stories, fears, and challenges and to derive support from contact with other women. Via health professional facilitation, women were able to collectively develop strategies to address risk factor modification and achieve optimal cardiovascular health. No statistically significant changes in depression, anxiety, stress, cardiac control, role integration, perceived social support were found, however, descriptive and qualitative findings revealed decreases in anxiety and an increased sense of social support. Conclusions: On the basis of this study, a cardiac rehabilitation program tailored to the needs of women appears to be feasible and acceptable. The efficacy of this intervention to improve health-related outcomes needs to be tested in a randomized controlled trial.